Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada PT. Galuga Putra Mandiri Manado (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The Influence of Product Quality and Service Quality on Customer Satisfaction at PT. Galuga Putra Mandiri Manado. The purpose of this study is to analyze the extent to which product quality and service quality influence customer satisfaction at PT. Galuga Putra Mandiri Manado, both partially and simultaneously. Product quality is the consumer's perception of the quality of the oil products sold at PT. Galuga Putra Mandiri Manado Service quality is an overall evaluation of the service functions actually received by customers (technical quality) and how the service is delivered (functional quality). Customer satisfaction is the level of happiness a person feels after comparing the performance or results they experience with their expectations. The analysis method used multiple regression analysis, while the relationship between the two variables was determined using the correlation coefficient method and hypothesis testing using t and F tests. There were 80 respondents in this study. The results of the study indicate that product quality and service quality, both partially and simultaneously, have a positive effect on the customer satisfaction of PT. Galuga Putra Mandiri Manado.